AVALIAÇÃO DA QUALIDADE FÍSICA DO SOLO NA ÁREA EXPERIMENTAL DA UEMS DE MUNDO NOVO - SOUZA, Durval Kauê de Almeida,; OZORIO, Jefferson Matheus Barros,; CUNHA, Vinicius Estigarribia,; CASTILHO, Selene Cristina de Pierri,; MARRA, Leandro Marciano, (ANAIS DO ENIC, 2025)
-